Theoretical investigation on the solution of the single-phase flow instability among parallel U-tubes. (15th September 2021) - Hao, J.L.; Li, M.R.; Chen, W.Z.; Yu, L.; Ye, L.
Highlights: A theoretical analysis method is employed to solve the reverse flow problem. The effects of reducing heat transfer capacity of the ascending section are analyzed. The method is proposed to solve the reverse flow problem. Abstract: The single-phase reverse flow problem of the parallel U-tubes of the steam generator (SG) reduces the natural circulation capacity of the system and negatively affects the safety of the reactor. In response to these issues, a theoretical analysis method verified with the experimental data is used to reveal the key factors (the heat transfer in the ascending section) affecting the single-phase reverse flow of the parallel U-tubes in SG. On this basis, we investigate the possibility of relieving the problem of single-phase reverse flow by reducing the heat transfer capacity of the ascending section under low flow conditions. Compared with other factors, the critical mass flow rate (CMFR) of reverse flow can be effectively reduced by which is useful for delaying the occurrence of the reverse flow. These research results can provide relevant theoretical support for solving the problem of the reverse flow.